Electron and hole spectra in quantum wire with two quantum dots in the electric field - Makhanets, O.; Gryschyk, A.; Dovganiuk, M. (Condensed Matter Physics, 2007)
The energy spectrum of electron and hole is investigated in a complicated nanoheterosystem consisting of two cylindrical semiconductor quantum dots placed into semiconductor quantum wire. Quantum dots are separated by barrier-layer, which is under the action of a constant electric field. The dependencies of electron and hole energies on geometric parameters of quantum dots and electric field intensity are analysed.